The Performance of Reinforcement Concrete Beam Containing Palm Oil Fuel ASH (POFA) and Expanded Polystyrene (EPS) in Term of Flexural Behavior - Goh Duan Kai; Osman, Mohamad Hairi; Mayhyeddin, Mohd Eizzuddin (Progress in Engineering Application and Technology, 2022)
The high demands on concrete cause environmental pollution as the process of producing cement increase the emission of CO2. Besides, the high demand of mining nature aggregate for produce concrete will cause exploitation of natural resources. Palm oil fuel ash (POFA) and expanded polystyrene (EPS) were highly potential waste material that can act as the replacement materials to produce a high performance and ecofriendly concrete. Hence, the aim of this study was to investigate the ability of POFA and EPS act as the replacement materials in reinforcement concrete beam. The objectives of this study were to compare the compressive strength, investigate the flexural behavior and determine the optimum percentage of reinforcement concrete beam that containing POFA and EPS. The samples reinforcement beams sized 1000mm x 150mm x 150mm with substitution of 10%, 20% POFA and 10% EPS were produced to conduct the laboratory tests. Besides, the compressive strength test was carried out through concrete cube and the flexural test was carried out through the reinforcement beam. It found that the workability of concrete mix decreased as the percentages of POFA and EPS added increased. The mass was shown decreased when the beam samples contained POFA and EPS. For the compression strength and flexural strength, it found that the sample contained 10% POFA had a better performance and the sample contained 10% POFA and EPS had a similar performance with normal concrete. Although the 10% POFA and EPS sample had the similar performance in strength, it was still more valuable than normal concrete since it was more low density, eco-friendly, low cost and the strength performance maintained.